IMPLEMENTASI PEMBELAJARAN BERBASIS APLIKASI GOOGLE CLASSROOM PADA PELAJARAN MATEMATIKA KELAS XI AKL 1 SMK NEGERI 1 PAMEKASAN - Purnamawati Purnamawati (LPPM STKIP PGRI Sidoarjo, 2022)
The Covid-19 pandemic has had a significant impact on the education sector, including the implementation of online learning. Google classroom is one of the Learning Management Systems (LMS) that can be an option for teachers in carrying out learning and communicating with students online. One way that can be used to carry out the online learning process is to use Google Classroom. Google Classroom-based learning can be accessed by all students through a google account. Based on the implementation carried out, the advantages of Google Classroom-based Mathematics learning are first, the set up process in Google Classroom is very fast and convenient. Second, using Google Classroom saves time. Third, improve cooperation and communication. Fourth, centralized data storage, all of which are in one centralized location in a specific folder. Fifth, fast resource sharing. Sixth, the teacher can create a list of student attendance in the form of a link using the Google Form application and then send it to Google Classroom.